WATER HEATER BERTENAGA MATAHARI MENGGUNAKAN REFLEKTOR - Tia Fatiha; Muhammad Fajri Rinaldy; Ocsirendi; Surojo (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Indonesia is one of the countries in the world that is crossed by the equator that cause Indonesia has a duration of 12 hours (or all day). Hence, the sun can be alternative energy. For instance, it can be used for heating water. Water heaters circulating in the market are still priced in quite an expensive range, so innovation is needed. In this research, a tool is made namely a Solar Water Heater which can track the direction of the sun's rays with the addition of a reflector to reflect sunlight to get optimum heat. This study aims to see the difference between a continuous water cycle where the pump will continue to pump water into the tank through a hot cross-section with a delayed water cycle where the pump will stop for 10 seconds so that the water sits on the copper pipe first. Based on the test results, it was found that the Solar Water Heater can heat water in the tank up to 47.35 degrees Celsius in unstable weather and the optimum method for heating the water is the continuous method which has a difference of 6,47 degrees Celsius with the delay method.